Health Workforce Assessment in Jakarta for Effective HIV Policy Implementation: Challenges and Opportunities toward Epidemic Control - Deussom, Rachel Hoy (Jurnal Ekonomi Kesehatan Indonesia, 2018)
Strategic efforts are needed in Indonesia to implement the recently released human immunodeficiency virus (HIV) Test and Treat policy which promotes increased treatment uptake, known to have important economic benefits. Of Indonesia’s estimated 631,635 people living with HIV (PLHIV) in 2018, only 12% are on treatment. The USAID- and PEPFAR-funded Human Resources for Health in 2030 (HRH2030) Program undertook policy analysis and assessed the available health workforce and service delivery at select sites in Jakarta to identify and anticipate Test and Treat implementation gaps. A mixed methods concurrent triangulation design was used, including policy analysis, key informant interviews, and site-level tools to capture workforce availability, skills, quality, and performance. Results indicate priorities to: define and implement HIV standards of practice for the Test and Treat policy; improve relevance and coordination of pre-service and in-service training programs; and support managers to optimize task and workforce allocation, including allocating lower-skilled workers to routine testing. Additional site-level data are needed from rural and remote sites in Indonesia, where fewer health workers are distributed. Efficiencies can help sustain HIV programs and contribute to epidemic control.